Formula milk increases lactoferrin levels in 7–9 years old children - L. Luthfiani; Dwi Suryanto; Suzanna Sungkar (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2021)
Background: Lactoferrin is known to have a bacteriostatic or bactericidal effect by binding ions in saliva to interfere with the survival of bacteria that need such ions, such as Streptococcus mutants. Lactoferrin is a whey protein and can be found in formula milk. Purpose: This study aimed to analyse lactoferrin levels before and after consuming formula milk and sterilized milk. Methods: This study was conducted on 22 students aged 7–9 years at Public Elementary School (SD Negeri) 060817 using purposive sampling, with 11 students consuming formula milk and 11 students consuming sterilized milk. Saliva was collected by the spitting method before and after consumption on the first and seventh days. Examination of lactoferrin levels was done using the Enzyme-Linked Immunosorbent Assays (ELISA). Differences in lactoferrin levels in each group before treatment on day one and day seven were analysed using the Friedman and analysis of variance (ANOVA) tests. Differences in lactoferrin levels between the formula milk and sterilized milk groups were analysed using the independent sample t-test and the Mann-Whitney test (p<0.05). Results: The average levels of lactoferrin before consuming formula milk was 0.212 ± 0.034 mg/100ml and increased to 0.222 ± 0.036 mg/100ml and 0.315 ± 0.026 mg/100ml. In the sterilized milk group, lactoferrin levels increased from 0.216 ± 0.033 mg/100ml to 0.225 ± 0.032 mg/100ml and 0.235 ± 0.027 mg/100ml. The increase in lactoferrin levels was more significant in the formula milk group on the seventh day (p=0.001, p<0.05). Conclusion: Formula milk, which contains whey protein, has a high potential in increasing lactoferrin levels.